The effect of an 8 week neuromuscular training program on knee movement biomechanics in African American female athletes - Hughley, T. W.; Johnson, J.; Ford, K. R.; Yoon, A (International Journal of Applied Sports Sciences, 2021)
This study examined the effects of an eight-week neuromuscular training (NMT) program on knee valgus angle in African American female athletes. Twenty-six female collegiate athletes participated. NMT group (n=15, 19.6±1.12 years) underwent an intervention training program that included three main components (plyometric and movement, core strengthening and balance, and resistance training). While, control group (n=11, 19.3±1.50 years) underwent the resistance training protocol for eight weeks. We hypothesized the NMT program would significantly decrease knee valgus angles during a drop vertical jump (DVJ) at landing for the NMT group when compared to the control group. Wilcoxon signed rank tests were done on the Pre-and Post-test findings. Results showed maximum valgus angle (VGmax) is significantly decreased (p<.05), and Maximum flexion (Flexmax) is significantly increased during the drop vertical jump in dominant leg (p<.05). The results support the hypothesis that an 8-week NMT program that combines injury prevention-training components can decrease an injury risk factor such as knee valgus in African American female athletes.